Urbanisation and landscape juxtapositions in Minas Gerais, Brazil: revisiting historical cartographies - Capanema Alvares Fernandes, Patricia (International Planning History Society Proceedings, 2016)
The recent discussions following the biggest mining disasters in Minas Gerais bring to the fore the paradoxical relations between economical development versus ecological collateral damages of mining which are central in Minas Gerais, a state that carries mining in is name. The issue is of course embedded in the latent global debate that opposes development and environment. When radical soil transformations - including mining and urbanisation - are extensively performed in the name of development the question of social and ecological resilience becomes crucial. Since the eighteenth century colonial gold rush, urban and territorial development in the region, rich in gold and iron ore, has long been paired with topographical manipulations related to the extraction of these prime resources. These processes have created a landscape of addition and subtraction, where extraction becomes entwined also with the creation of urban fragments. Belo Horizonte, a city created from scratch in the end of the 19th century was no exception. To found the capital of Minas Gerais state, a territory of significant topographical features was soon confronted with the symmetrical array of perpendicular and diagonal streets proposed by the plan of 1895. Over its history, extreme manipulations of ground-surface conditions have not been limited to mining activities but are largely performed to allow urbanisation to take place in the form of heterotopic housing entities. Before the foundational grid had been fully laid out, its first metropolitan extension took place 12 quilometres from ground zero as a elite targeted satellite town around a new lake resulting from the damming of the river Pampulha. The case of Pampulha is exemplary of the critical entwinement between enclaved settlement formation, artificial ground operations, water storage production and social-ecological resilience in Belo Horizonte, offering an inspiring terrain for re-imagining projectively the conflicts between human settlement and ecological cycles. By combining archival material with descriptive and interpretative mappings, this paper will address Pampulha’s emergence and historical development as the spearhead of the entanglement of enclaved urbanism and artificial topographies that is currently a dominant form of urbanisation in Brazil. Aiming to understand the complexity in the processes of transforming earth into land, territory is approached as a palimpsest, combining archival material with descriptive mappings done within the scope of the doctoral research. (Corboz 1983, Harley 1989)